1991
DOI: 10.1007/bf00230527
|View full text |Cite
|
Sign up to set email alerts
|

Changes in striatal dopamine neurohistochemistry and biochemistry after incomplete transient cerebral ischemia in the rat

Abstract: To evaluate the development of striatal ischemic cell damage in relation to alterations in dopamine (DA) transmission, one year old male Wistar rats underwent a 15 min incomplete cerebral ischemia (ICI) induced by occlusion of the common carotid arteries and by hypovolemic hypotension. The animals were divided into the following experimental groups: sham operated rats, rats with ICI without reperfusion, and rats with ICI followed by 60 min, 24 h, 72 h and 144 h of recirculation. The ischemia induced striatal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Striatal neurons, particularly small-to medium-sized ones, have been shown to attain ischemic cell change more rapidly than cortical and hippocampal neurons (20). This early degeneration of small-to medium-sized striatal neurons has been related to changes in striatal dopamine neurohistochemistry (21). It may be that repeated insults enhance these early ischemic cell changes, sensitizing striatal neurons in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal neurons, particularly small-to medium-sized ones, have been shown to attain ischemic cell change more rapidly than cortical and hippocampal neurons (20). This early degeneration of small-to medium-sized striatal neurons has been related to changes in striatal dopamine neurohistochemistry (21). It may be that repeated insults enhance these early ischemic cell changes, sensitizing striatal neurons in particular.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are in line with previous reports of enlarged granular TH terminals and large synaptophysin-positive dots after cerebral ischemia/reperfusion in the rat CPu (Sabogal et al, 2014). This phenomenon was considered as a compensatory function of the dopaminergic nerve terminals in response to the striatal neuron degeneration (Nemeth et al, 1991;Korematsu et al, 1993). An earlier study reported that salidroside upregulated the expression of dopamine transporter in the striatum in an animal model of a neurodegenerative disease (Li and Chen, 2019).…”
Section: Discussionmentioning
confidence: 99%